The Relationship between Machinery and Steel Production in Russia and the United States - Kasdan, Saul (The Review of Economics and Statistics, 1952)
SOVIET Russia can serve as an extremely fascinating case study in the field of economic development-a field where scientific curiosity is certainly not matched by available statistical data, and where a good deal of ingenuity or foolhardiness is needed for the construction and evaluation of estimates from scattered pieces of information. In studies of economic development a method frequently used for checking estimates and establishing their comparative importance consists of applying the lessons of the past experience of some advanced country (such as the United States) to economically younger areas. Our present knowledge of economic development is insufficient for a final evaluation either of this method as a whole or of its applications, especially in the case of countries whose economic development has been unique. But attempts to draw such comparisons, whatever their direct validity in specific cases may be, appear promising and useful as a source of material from which a theory of economic development can be gradually constructed. This problem came up during the recent controversy regarding the validity of the Soviet machinery index which took place in this REVIEW between Professor Gerschenkron and Mr. Dobb.2 Gerschenkron maintains that the official Soviet index of machinery output based on I926-27 weights is overstated, essentially because new machinery, not yet produced in 192627, was subsequently included in it at inflated prices. He presented the following comparison between the machinery index and an index of ferrous metals in Russia: I As shown in column (3), the ratio of ferrous metals to machinery fell drastically between I928 and I932; and for the whole period I92838, output of ferrous metals increased 5.4 times, while that of machinery increased I6.4 times. While a part of this divergence could be due to an increased degree of fabrication involved in production of machinery as compared with other metal-using industries, Gerschenkron felt that the ratio of I6.4 to 5.4 was too large to be explained by actual experience.4 Hence, he con-